Green employees’ relation practices and organisational sustainability of selected oil companies in South-South Nigeria - Godbless, Eromafuru, Edward; Igiagbe, Ikpea, Joseph (International Journal of Management and Sustainability, 2025)
This study examined the interlinkage between green employee relations practices and organizational sustainability of selected oil companies in South-South Nigeria. Anchored on human capital and resource-based theories, the research assessed the effect of green recruitment, green training, green performance appraisal, and green compensation on the sustainability of the Nigerian oil industry. The population comprised 1,318 employees across five selected oil companies in the oil-rich region of Nigeria, with a sample size of 307 determined through Taro Yamane’s technique and the table of random numbers. The reliability and validity of the research instruments were confirmed. Data were analyzed using descriptive and inferential statistics, with multiple regressions deployed to test the hypotheses. Findings revealed significant positive relationships between: green recruitment and organizational sustainability (β = 0.256, t = 7.540); green training and organizational sustainability (β = 0.115, t = 4.491); green performance appraisal and organizational sustainability (β = 0.662, t = 19.130); and green compensation and organizational sustainability (β = 0.096, t = 3.631). The study emphasizes the strategic importance of institutionalizing green hiring, green training, green reward structures, and green appraisal systems as essential strategies to promote and enhance the long-term sustainability of oil companies in the South-South geopolitical zone of Nigeria.